Simulation of erbium doped fiber amplifer (EDFA) - 294542 Teng, Kean Kah (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of ELectrical Engineering) - Universiti Teknologi Malaysia, 1999